Implementation of Corporate Social Responsibility and Communication (CSR) at PT. Pertani (Persero) - Ririn Frebianti; Nurita Andriani; Muh. Syarif (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Implementation of Corporate Social Responsibility and Communication (CSR) at PT. Farmers (Persero). This research is a qualitative descriptive research. This type of research is not to elaborate explanations, control communication symptoms or make predictions, but rather to provide an overview and understanding (understanding) of how and why a symptom or reality of communication occurs. The data collection technique used in this study was in-depth interviews. This type of interview contains questions that are